Mental Health Status of Youth Diagnosed With ASD Who Received Early Intensive Behavioral Intervention as Young Children. Issue 2 (3rd April 2021) - Koudys, Julie; Perry, Adrienne; Ho, Hilda S. W.; Charles, Meisha
Abstract: Many youth diagnosed with autism spectrum disorder (ASD) experience comorbid mental health issues. However, treatment history is rarely reported in these samples making it impossible to determine whether there is any relation between treatment history and later mental health functioning. Further, studies that report on outcomes of early intensive behavioural intervention (EIBI) rarely report long-term outcomes or mental health outcomes. This means that very little is known about the mental health status of children who previously received EIBI. This brief report describes the mental health profiles of 12 youth diagnosed with ASD who previously received EIBI, including measures of internalizing and externalizing disorders, and specific anxiety symptoms. The majority of participants (approximately 70%) were not experiencing significant mental health difficulties (reported by youth, parents and teachers). However, group mean scores for internalizing difficulties were significantly worse than those of the normative sample (reported by parents and teachers).